1984
DOI: 10.1136/hrt.51.4.445
|View full text |Cite
|
Sign up to set email alerts
|

Acute haemodynamic and metabolic effects of felodipine in congestive heart failure.

Abstract: SUMMARY Felodipine is a new calcium antagonist with a high degree of vascular selectivity. To examine its potential value as an afterload reducing agent in congestive heart failure 11 patients were studied. Substantial increments in cardiac index were associated with a fall in systemic vascular resistance. Left ventricular end diastolic pressure was also significantly reduced. Although left ventricular maximum dP/dt remained unchanged, maximum dP/dt/P increased. Left ventricular unloading was reflected by a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1985
1985
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Felodipine was reported to have negligible negative inotropic effects and high selectivity to smooth muscle [56]. The short-term administration of felodipine in patients with CHF during the resting state resulted in a reduction in SVR and blood pressure along with elevated LV filling pressure and an increase in cardiac output [57][58][59][60]. Studies examining the long-term effects of felodipine in chronic CHF have demonstrated hemodynamic benefits similar to those seen during short-term administration [61][62][63][64].…”
Section: Elkayammentioning
confidence: 91%
“…Felodipine was reported to have negligible negative inotropic effects and high selectivity to smooth muscle [56]. The short-term administration of felodipine in patients with CHF during the resting state resulted in a reduction in SVR and blood pressure along with elevated LV filling pressure and an increase in cardiac output [57][58][59][60]. Studies examining the long-term effects of felodipine in chronic CHF have demonstrated hemodynamic benefits similar to those seen during short-term administration [61][62][63][64].…”
Section: Elkayammentioning
confidence: 91%
“…Similar results have been found after intracoronary administration of felodipine to patients undergoing coronary angiography. Negative inotropic effects could not be demonstrated in patients with coronary artery disease (Culling et al 1984;Saltiel et al 1988;Sheridan & Culling 1985;Timmis et al 1984a). Usually, pharmacokinetic studies are performed in healthy volunteers, but as the kinetics of a drug can be influenced by age, disease, and other concomitant properties, further analysis is needed (Peck 1990;Sham mas & Dickstein 1988).…”
Section: Dosage-effect and Concentration-effect Relationshipsmentioning
confidence: 96%
“…The Prospective Randomized Amlodipine Survival Evaluation (PRAISE), which enrolled 1,153 patients with severe chronic heart failure, found that amlodipine, a long-acting dihydropyridine, had neutral effects (similar to placebo) although it may have been of benefit in the subgroup with nonischemic heart failure [23]. Although early indications suggested that other dihydropyridines selective for the vasculature such as felodipine, nicardipine and nisoldipine would provide short-term alleviation of CHF symptoms, long-term studies have failed to substantiate these initial promising results [24][25][26].…”
Section: Calcium Antagonistsmentioning
confidence: 99%